A prospective study of risk factors for hamstring injury in Australian football league players. Issue 12 (18th June 2021) - Smith, Nigel A.; Franettovich Smith, Melinda M.; Bourne, Matthew N.; Barrett, Rod S.; Hides, Julie A.
ABSTRACT: This study aimed to explore the association between hamstring strength, age and lower limb soft tissue injury history and subsequent hamstring injury among Australian Football League (AFL) players. This prospective cohort study recruited 125 players from three professional AFL teams. Eccentric knee flexor strength was assessed while performing the Nordic hamstring exercise in pre-season, and injury data were collected retrospectively (hamstring, groin, calf, quadriceps and knee), and prospectively (hamstring injuries) for one AFL playing season. Fourteen players (11%) sustained a hamstring injury in the subsequent playing season. Nordic strength was not significantly associated with future hamstring injury (Odds Ratio (OR) 1.9, p = 0.36), whereas player age greater than 25 years (OR = 2.9, p < 0.05), report of a hamstring injury within the previous year (OR = 3.7, p = 0.01), or greater than 1-year (OR = 3.6, p = 0.01), a previous groin (OR = 8.6, p < 0.01) or calf injury (OR = 4.6, p = 0.01) were factors significantly associated with subsequent hamstring injury. Based on these findings, increasing age and previous hamstring, groin and calf injury are all associated with an elevated risk of subsequent hamstring injury in AFL players.